2009
DOI: 10.1097/ijg.0b013e31819c4893
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Effect of Intravitreal Injection of Ranibizumab (Lucentis) on Intraocular Pressure

Abstract: IVIL causes a considerable short-term transient rise in IOP. The IOP increase after IVIL can be statistically significant at 0 to 30 minutes after injection in both phakic and pseudophakic eyes, and tends to be greater in shorter eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
2
18

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 25 publications
2
67
2
18
Order By: Relevance
“…29 Intraocular pressure elevation Acute rise of intraocular pressure (IOP) after intravitreal injection is injectionprocedure-related and lasts a few hours at most. 30,31 Recent studies, however, have reported a significant number of intravitreal anti-VEGF injections is associated with an increased risk for IOP elevation. 32,33 Patients with pre-existing glaucoma have higher rates of IOP elevation compared with those without pre-existing glaucoma.…”
Section: Methodsmentioning
confidence: 99%
“…29 Intraocular pressure elevation Acute rise of intraocular pressure (IOP) after intravitreal injection is injectionprocedure-related and lasts a few hours at most. 30,31 Recent studies, however, have reported a significant number of intravitreal anti-VEGF injections is associated with an increased risk for IOP elevation. 32,33 Patients with pre-existing glaucoma have higher rates of IOP elevation compared with those without pre-existing glaucoma.…”
Section: Methodsmentioning
confidence: 99%
“…In order to investigate the immediate short-term effects of anti-VEGF injection on IOP, Gismondi et al [9] performed a prospective study of 54 eyes with intravitreal ranibizumab. In that study, the IOP was measured immediately before as well as 5 s and 5, 10, 15, 30 and 60 min and 1 day after injection.…”
Section: Introductionmentioning
confidence: 99%
“…Bu yan etkilerden biri de ani GİB artışıdır. Artmış vitreus volümüne bağlı olarak enjeksiyondan hemen sonra GİB artışı beklenen bir durum olup çeşitli çalışmalarda geçici veya kalıcı özellikte olabileceği bildirilmiştir [5][6][7][8][9]. Daha önceki çalışmalara benzer şekilde bizim çalışmamızda da enjeksiyondan hemen sonra GİB'de anlamlı bir artış olduğu ve 24. saatte bu artışın normal değerlerine geri döndüğü izlendi.…”
Section: Discussionunclassified
“…Enjeksiyon ile ilgili (uygulanan enjeksiyon volümü, ve enjeksiyon sonrası reflü) ve göz ile ilgili (aksiel uzunluk, skleral rijidite, vitreus yapısı) faktörlere bağlı olmak üzere neredeyse tüm intravitreal enjeksiyonlardan sonra ortaya çıkan bir yan etki de ani göziçi basıncı (GİB) artışıdır [5][6][7][8][9]. Enjeksiyon sonrası ani GİB artışı ve oküler aksiyel uzunluk (AU) değişikliği ile ilgili çok sayıda çalışma bulunmasına karşın lensin, glokom mevcudiyetinin ve daha önceden enjeksiyon uygulanmış olmanın bu değişiklikler üzerindeki etkisini ortaya koyan bir çalışma bulunmamaktadır [6,10,11].…”
Section: Introductionunclassified